Evaluación técnica de la instalación del horno industrial en la panadería central para fabricación de pan bajo las reglas del retie en el municipio de Tibú Norte de Santander (2020)
A total arrangement of the oven of the central bakery in Tibú, Norte de Santander will be prepared since it is in poor condition due to aging, temperature issues, etc. The oven has an electrical system that is currently in poor condition and can cause many damages, even too costly, and can even cause the death of a worker since its condition is very delicate. The main objective of this project is to identify the current conditions of the state of an industrial oven used for the baking of bread in the Central Bakery in Tibú, to later propose alternatives to adapt the infrastructure, power lines and everything that is to our scope, through electrical drawings and complying with current regulations. In addition, the project indicates the implementation of preventive maintenance for the industrial furnace as a key element of competitiveness and quality, as well as the importance of knowing the preventive maintenance procedures for industrial furnaces in production.